Subtitling Strategy of Interrogative Sentences in Vivo Movie - Dewi Wulan Sari (Asosiasi Dosen Muda Indonesia, 2023)
Subtitling is the process of transferring the equal meaning of what is being said in the movie as a source language into the target language. The product of its process is called as subtitle. The aims of this research are to find out the types of subtitling strategy applied in the interrogative sentence in Vivo movie and to found out the most frequent subtitling strategy applied in the interrogative sentence in Vivo movie. The source of the data in this research is Vivo movie while the data are the interrogative sentence in Vivo movie. The researcher uses descriptive qualitative research method. Gottlieb’s theory is applied in this research. The result shows that out of 92 found, 7 subtitling strategies are applied in Vivo movie, they are expansions (2), paraphrases (14), transfers (51), imitations (8), condensations (7), decimations (5), and deletions (5). The most frequent subtitling strategy used is transfer.